RATIONALIZING THE ROLE OF THE UNIVERSITY AS AN ACTOR OF THE AGRICULTURAL INNOVATION ECOSYSTEM - Prisacaru, Veronica; Ivanova, Tatiana (CEP USM, 2023)
The goals of the research were the following: elucidation of the concept of the innovation ecosystem and of the importance of the agricultural innovation ecosystem; highlighting the role of the universities as innovation ecosystems` actors; synthesis of the cuttingedge innovative approaches in the agricultural ﬁeld and, on this basis, formulating recommendations for curriculum improvement. In order to achieve the mentioned goals, the following research methods were applied: synthesis of the conceptual approaches and of some practical studies related to the research object, opinion survey, inductive method, analysis, generalization, systematization, for-mulation of reasoning and recommendations. As a result of the research, the directions of intervention in the agricultural undergraduate degree programs were identiﬁed in order to facilitate the exercise by the professional educational service providers of the role of active and eﬀective actors of the innovation ecosystem. The research was carried out within the project “Predictive approaches to increasing the quality of skills in agricultural higher education based on the partnership with the business environment”, No. 20.80009.0807.41, contracting authority - National Agency for Research and Development.
RAȚIONALIZAREA ROLULUI UNIVERSITĂȚII CA ACTOR AL ECOSISTEMULUI DE INOVAȚIE AGRICOLA
Keywords: agriculture; curriculum; education; innovation ecosystem; skills